Inclusion of premenopausal women in breast cancer clinical trials. (December 2022) - Corrigan, Kelsey L.; Kouzy, Ramez; Jaoude, Joseph Abi; Patel, Roshal R.; Layman, Rachel M.; Giordano, Sharon H.; Woodward, Wendy A.; Smith, Benjamin D.; Shaitelman, Simona F.; Ludmir, Ethan B.
Abstract: Background: Patients with premenopausal breast cancer (PMBC) have been historically excluded from some clinical trials because of the limitations of using endocrine therapy (ET) in this population. We analyzed breast cancer randomized clinical trials (RCTs) to determine the rates of and factors associated with inclusion of PMBC patients to provide a benchmark for PMBC inclusion in RCTs moving forward. Methods: Using ClinicalTrials.Gov, we identified breast cancer phase III RCTs and extracted inclusion criteria and patient enrollment information. Multiple binary logistic regression modeling was used to assess trial-related factors that were associated with PMBC patient inclusion. Results: Of 170 breast cancer RCTs identified, 131 (77.1%) included PMBC patients. Sixty-five (38.2%) trials analyzed patients with hormone-receptor-positive (HR+) and HER2-negative (HER2-) breast cancer, of which 31 (47.7%) allowed for enrollment of PMBC patients. Lower rates of PMBC inclusion were seen in trials that studied HR+/HER2-patients (47.7% PMBC inclusion in HR+/HER2-trials vs. 94.3% in non-HR+/HER2-trials, aOR 0.07 [95% CI: 0.02–0.19], p < 0.001) and in trials that randomized or mandated ET (44.4% in ET trials vs. 83.2% in non-ET trials, aOR 0.21 [95% CI: 0.10–0.83], p = 0.02). Trials studying chemotherapy (CT) were associated with inclusion of PMBC patients (100% in CT trials vs. 70.5% in non-CT trials, a OR 14.02 [95% CI: 1.54–127.91], p = 0.01). All surgical and radiation therapy clinical trials allowed for the inclusion of PMBC patients in their eligibility criteria. Conclusions: Breast cancer clinical trials should carefully select their enrollment criteria and consider inclusion of premenopausal patients when appropriate. Highlights: We investigated the inclusion of premenopausal breast cancer (PMBC) patients in clinical trials. There was lower inclusion of PMBC in trials studying HR+/HER2-patients. There was lower inclusion of PMBC in trials studying endocrine therapy. Trials should carefully select their enrollment criteria and include PMBC patients when appropriate.